ANALYSIS OF FINANCIAL PERFORMANCE USING THE DU PONT SYSTEM AT PT PEGADAIAN (PERSERO) - T. M. Iqbal Rafliyazid. F; Ruzikna ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to determine the financial performance of PT. Pegadaian (Persero) using the Du Pont System for the 2017-2021 period. This study uses a quantitative-descriptive analysis method. Data collection through documentation using financial reports. The research data was obtained from www.pegadaian.co.id. The data analysis technique used is the Du Pont System analysis which consists of Net Profit Margin (NPM), Total Asset Turnover (TATO), Multiplier Equity (ME), Return on Investment (ROI), Return on Equity (ROE). The results of the study show that the Net Profit Margin (NPM) analysis for 2017-2021 gets a good predicate, from the Total Asset Turnover (TATO) analysis it gets a bad predicate, from the Multiplier Equity (ME) analysis it gets a very good predicate, from the Return on Investment (ROI) analysis it gets a bad predicate, and from the Return on Equity (ROE) analysis it gets a good predicate. Keywords: Financial Performance, Du Pont System